2013
DOI: 10.1186/1465-9921-14-40
|View full text |Cite
|
Sign up to set email alerts
|

The Tiotropium Safety and Performance in Respimat® Trial (TIOSPIR®), a large scale, randomized, controlled, parallel-group trial-design and rationale

Abstract: BackgroundTiotropium bromide is an effective therapy for COPD patients. Comparing across programs tiotropium Respimat® Soft Mist™ inhaler was at least as efficacious as tiotropium HandiHaler®, however, concerns have been raised about tiotropium’s safety when given via Respimat®.MethodsThe TIOSPIR® trial (NCT01126437) compares the safety and efficacy of tiotropium Respimat® 5 μg once daily (marketed) and 2.5 μg once daily (investigational) with tiotropium HandiHaler® 18 μ once daily (marketed). The hypotheses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 10 publications
0
51
0
4
Order By: Relevance
“…In the TIOSPIR trial, some seven inclusion and 29 exclusion criteria were applied to define the study population . In total, 21 of these criteria were reproducible in our database.…”
Section: Methodsmentioning
confidence: 99%
“…In the TIOSPIR trial, some seven inclusion and 29 exclusion criteria were applied to define the study population . In total, 21 of these criteria were reproducible in our database.…”
Section: Methodsmentioning
confidence: 99%
“…The TIOSPIR (Tiotropium Safety and Performance in Respimat) trial (NCT01126437) in 17 135 patients with COPD confirmed that the safety profiles of tiotropium 5 µg and 2.5 µg delivered via the Respimat inhaler (hereinafter referred to as tiotropium Respimat) were comparable with those of tiotropium 18 μg delivered via the Spiriva HandiHaler device [53]. A number of studies have now evaluated the efficacy of tiotropium Respimat compared with placebo, each as an add-on to usual care with at least ICS in patients with symptomatic asthma.…”
Section: Tiotropium Add-on Therapy Delivered Via the Respimat Soft MImentioning
confidence: 79%
“…But, subsequently a larger randomised-controlled trial comparing this effect in patients receiving tiotropium by Respimat or HandiHaler (which was deemed to be safe by the time), found no difference as far as mortality due to device was concerned. 21,22 Searching Newer Therapeutic Targets-COPD is a systemic disease and has different arms of pathogenesis. In due consideration, the treatment demands the search of such therapeutic targets other than the conventional bronchodilators namely LABAs and LAMAs.…”
Section: Review Of Literature Newer Innovations In Pharmacotherapy-mentioning
confidence: 99%